Supervision in Education for Effective Teaching in Nigeria Secondary Schools - Ogunwale, Ogundiran Samuel (NIU Journal of Humanities; Vol 3 No 4 (2018): KIU Journal of Humanities, Vol. 3 No. 4, December 2018, 2019)
This paper discussed effective supervision and teachers’ attitude towards teaching in Nigerian Secondary schools. It identified effective instructional supervision as one of the mechanisms to be put in place towards achieving the goals in the school system. The paper also examined major challenges of instructional supervision in secondary schools and the way forward among other issues discussed. Relevant literature were reviewed, recommendations were made on how to ensure effective supervision of instruction secondary schools and a conclusion was drawn that successful supervisors should be knowledgeable about educational leadership, management and administration, and should be knowledgeable of real life issues which should be built on the supervisor's thorough understanding and in- depth knowledge of instructional theory and not on a check list of what should be in a lesson. Keywords: Effective Supervision, Teachers’ Attitude and Teaching